SAT0141 Safety of Anti-TNFS in RA Patients in Real Life: Results from a Systematic Litterature Review and Meta-Analyses from Biologic Registers. (9th June 2015) - De la Forest, M.; Brugneaux, J.; Utard, G.; Salliot, C.
Abstract : Background: In daily practice safety in rheumatoid arthritis (RA) patients receiving biological treatment is an important issue. Unlike randomized controlled trials, biologic registers provide real life safety data. Objectives: To identify biologic registers worlwide, to collect and analyze data regarding safety in RA patients under anti-TNF treatments. Methods: Up to December 2014 and according the Cochrane Collaboration Guidelines, systematic review was performed independently by 2 rheumatologists using PUBMED, EMBASE and Cochrane library databases. Worldwide biologic registers were identified and publications regarding safety issues in RA patients were included (mortality, cardiovascular events, cancer including lymphoma and melanoma and serious infections). Fixed-effect meta-analyses were performed to compare safety events between 1) biological agent and non biological DMARD (nbDMARD), 2) anti-TNFs. Pooled odds ratios (ORs) were calculated, using the Mantel–Haenszel method with a continuity correction. Results: 43 biological registers were identified wordwide corresponding to 322 publications in PUBMED and EMBASE. From 114 publications on safety in RA patients receiving anti-TNF, 40 were included for meta-analyses. Compared to nbDMARD, mortality and cardiovascular events were significantly descreased in patients treated with anti-TNFs (OR=0.77 [95%CI 0.70-0.85] and OR=0.60 [0.51-0.71]), respectively). Anti-TNFs did not increase the risk of cancer in patients without or with prior malignancy (OR=0.70 [0.64-0.75] and OR=0.81 [0.42-1.55], respectively), lymphoma (OR=0.87 [0.65-1.16]) and melanoma (OR=2.46 [0.70-8.65]). As expected, serious infections were significantly increased during anti-TNF treatment (OR=1.60 [1.47-1.75]) compared to nbDMARD. Soluble receptor to TNF (etanercept) would lead to less serious infections than infliximab (OR=0.82 [0.73-0.92]), without significant difference compared to adalimumab (OR=1.22 [1.08-1.37]). Conclusions: By reducing dramatically chronique inflammation in RA patients, anti-TNFs descrease mortality, cardiovascular events without increase significantly the risk of cancer, compared to nbDMARDs. Disclosure of Interest: None declared